The Effect of Carbon on Chitosan-ZnO Composites as Fabric Mask Coating Materials - Mauliana, Metatia Intan; Findawati , Yulian; Hanum, Galuh Ratmana (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Increasing the effectiveness of cloth masks can reduce the use of disposable medical masks which creates a new waste problem. In this research, the synthesis of zinc oxide nanoparticles was carried out using the precipitation method through the reaction between zinc nitrate and phosphoric acid as one of the ingredients in the chitosan-ZnO/C composite mixture. The carbon source is obtained from activated coconut shell carbon using sodium hydroxide. X-ray diffractometer (XRD) testing was carried out to determine the phase content of the synthesized carbon powder. XRD testing was also carried out on synthesized ZnO particles to determine the occurrence of phase transformations and to determine the quantitative and qualitative characteristics of the material. Fourier Transform Infrared testing was also carried out to observe functional group bonds formed in carbon compounds. Composite materials that have been successfully made will then be tested for hydrophobicity by calculating the contact angle. The results of this study indicate that the synthetic base material has been successfully carried out and the composite has been successfully made. The highest water contact angle is 106o was found in the chitosan/ZnO composite sample with a ratio of 2:1 and a mass variation of 0.05 gr active carbon.